2016
DOI: 10.1099/ijsem.0.001100
|View full text |Cite
|
Sign up to set email alerts
|

Sphingobacterium zeae sp. nov., an endophyte of maize

Abstract: A yellow-pigmented strain (JM-1081 T ) isolated from healthy stem tissue of Zea mays was taxonomically characterized. Cells of the strain were rod-shaped and Gram-stain-negative. Comparative 16S rRNA gene sequence analysis revealed closest relationship to the type strains of Sphingobacterium multivorum (98.1 % similarity), Sphingobacterium mucilaginosum (97.9 %) and Sphingobacterium siyangense (97.8 %). 16S rRNA gene sequence similarities to the type strains of all other Sphingobacterium species were below 97.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Different taxon profiles between generalist edges and specialist edges linking generalist vertices suggest that generalist taxa could display different co-occurrence patterns along different environments. We found that the most abundant generalist edges were all linked with Sphingobacterium, which are ubiquitous in soil [26], water [27], and animal [28] or plant-associating microbiomes [29]. However, ubiquitous existence cannot guarantee formation of generalist edges since substantial specialist edges linked generalist vertex pairs.…”
Section: Discussionmentioning
confidence: 88%
“…Different taxon profiles between generalist edges and specialist edges linking generalist vertices suggest that generalist taxa could display different co-occurrence patterns along different environments. We found that the most abundant generalist edges were all linked with Sphingobacterium, which are ubiquitous in soil [26], water [27], and animal [28] or plant-associating microbiomes [29]. However, ubiquitous existence cannot guarantee formation of generalist edges since substantial specialist edges linked generalist vertex pairs.…”
Section: Discussionmentioning
confidence: 88%
“…Of these, Microbacteriaceae, Comamonadaceae and Flavobacteriaceae have been found to be abundant in barley root (Bulgarelli et al 2015). Sphingobacteriaceae are known to be endophytes of maize (Kämpfer et al 2016). Microbacteriaceae and Oxalobacteriaceae are reduced under submergence, whereas there were more Bacillaceae (Fig.…”
Section: Sensitive and Tolerant Barley Accessions Show Specific Bacte...mentioning
confidence: 99%
“…The genera Chitinophaga, Chryseobacterium, and Sphingobacterium are common in several environments or in symbiosis with several groups of organisms; however, Chryseobacterium is also a pathogen associated with several diseases, being commonly found in anura skin related to infections in the group [68]. On the other hand, Chitinophaga and Sphingobacterium are commonly found in environmental samples of soil and water, also related to fungi and plants endosymbionts [69][70][71][72][73]. Loudon et al [54] showed that a Chitinophaga arvensicola isolate, together with a Bacillus sp., had a higher inhibitory effect against Bd compared to the Bacillus sp.…”
Section: A Distinctive Frog Foam Nest Communitymentioning
confidence: 99%